The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools - Mármol Cisneros, Juana Isabel (2012)
The theme of this research refers to “The use of supplementary materials in EFL classes”. The main purpose of this study was to determine and compare the type of supplementary materials that are being used in public and private high schools. This study was performed in the city of Santo Domingo de los Tsáchilas, for this research two high schools were selected at random, one public and one private. Five classes were observed in 1st, 2nd, and 3rd grades in both high schools respectively. The methods applied in this research were: qualitative to get descriptions of class observations and quantitative to compare the frequency of use of supplementary materials between public and private high schools. This study demonstrates that supplementary materials are not being used frequently in Ecuadorian public and private high schools. Being the visual aid (whiteboard) the most used supplementary material in both high schools. Moreover, teachers from public and private high schools only in some classes took into consideration the content of the class, the students’ level and their learning styles (visual, auditory, and kinesthetic).